2023
DOI: 10.3390/ani13071247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus Lactis Supplementation on Growth Performance, Hematological Parameters, Meat Quality and Intestinal Flora in Growing-Finishing Pigs

Abstract: Objective: The study was conducted to assess the effect of supplementation with Lactobacillus lactis (LL) on growth performance, hematological parameters, meat quality and intestinal flora in pigs from growing until slaughter. Methods: A total of 72 growing pigs (30.46 ± 3.08 kg) were randomly assigned to 3 groups (including 3 pens for each group, with 8 pigs in each pen). The three treatments comprised a basal diet (O-0) and two experimental diets supplemented for 14 weeks with 0.01% (O-100) and 0.03% (O-300)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…The results of our research show an increase in the growth of lactobacilli in pigs of the second group, having a positive effect on the total daily weight growth of growing pigs. The obtained data are consistent with the results of Duan et al (Duan et al, 2023). Instead, Huang et al demonstrated that the consumption of probiotics with lactobacilli in the composition effectively affects daily weight growth only during the first two weeks of life (Huang et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our research show an increase in the growth of lactobacilli in pigs of the second group, having a positive effect on the total daily weight growth of growing pigs. The obtained data are consistent with the results of Duan et al (Duan et al, 2023). Instead, Huang et al demonstrated that the consumption of probiotics with lactobacilli in the composition effectively affects daily weight growth only during the first two weeks of life (Huang et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Yu, et al [26] reported transient improvements in ADG and feed efficiency in newly weaned pigs supplemented with L. lactis in feed. Similarly, in a study by Duan, et al [27] grower-finisher pigs supplemented with L. lactis probiotic over 14 weeks, also demonstrated improved ADG during the grower period and improved final body weight at slaughter. The mode of administration is likely the reason for the differing outcomes, with orally administered probiotics more likely to reach the gastrointestinal tract where they can have a greater impact on growth performance.…”
Section: Discussionmentioning
confidence: 75%
“…BUN levels generally decrease when the protein mass and absorption are reduced [47]. Duan et al [48] reported that the grower phase, the control group (0%), had significantly lower BUN values than the 0.1% and 0.3% Lactobacillus lactis groups, whereas no difference was observed in the BUN values among the three groups for the finisher phase. For example, in the digestive tract, probiotics increase ammonia fixation and alleviate decreases in amino acid availability, which can be reduced by increasing the concentration of blood urea [49].…”
Section: Discussionmentioning
confidence: 99%